CONTENT MARKETING STRATEGY IN BUILDING ENGAGEMENT OF INSTAGRAM FOLLOWERS OF CEK FAKTA - Saffanah, Moura; Suryana, Asep (AT-TAWASUL, 2025)
The development of technology makes it easier for people to send information to each other, create information, and reduce information. The abundance of information is accompanied by the unstoppable growth of hoaxes. One of the efforts to counterbalance the spread of hoaxes is by spreading fact-checked news. So fact-checked news needs to be marketed with unique packaging and distributed through easy-to-use media with strategies aimed at building audience interaction and engagement with fact-checked news content. Engagement is an important factor to see the interest and response of the audience. The purpose of this study is to describe, analyze and understand the content marketing strategy of the @tempo.cekfakta Instagram account in building follower engagement. This research data collection was carried out using interview techniques to 6 research informants, observation of the @tempo.cekfakta account, documentation of concepts relevant to the research raised, and expert informants. The results of this study show that @tempo.cekfakta applies content marketing stages which include goal setting, audience mapping, content planning, content production, content distribution, content amplification, content evaluation, and content reinforcement in building follower engagement. It can be concluded that the engagement of @tempo.cekfakta followers can be higher than similar accounts due to the impact of the consistency of account uploads, the content format in the form of short videos, the use of hosts as storytellers, and the use of audiovisuals